2012
DOI: 10.1055/s-0032-1330847
|View full text |Cite
|
Sign up to set email alerts
|

Lisfranc Injury in Adolescents

Abstract: Lisfranc injuries in adolescents are likely to cause constant harm, even if the anatomical reduction is achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…Veijola et al 12 conducted a retrospective review of three male and three female patients with a mean age of 14.7 years within an age range of 13 to 16 years old at the time of evaluation; note, one patient had bilateral Lisfranc injures, totaling the amount of injured feet to seven. Impact from a height between 3 to 10 meters accounted for four Lisfranc injuries and the other three Lisfranc injuries were from motor vehicle accidents (MVA) involving motorcycles or scooters.…”
Section: Resultsmentioning
confidence: 99%
“…Veijola et al 12 conducted a retrospective review of three male and three female patients with a mean age of 14.7 years within an age range of 13 to 16 years old at the time of evaluation; note, one patient had bilateral Lisfranc injures, totaling the amount of injured feet to seven. Impact from a height between 3 to 10 meters accounted for four Lisfranc injuries and the other three Lisfranc injuries were from motor vehicle accidents (MVA) involving motorcycles or scooters.…”
Section: Resultsmentioning
confidence: 99%
“… 5 Similarly in children, a study of adolescent Lisfranc injuries found persistent pain and discomfort in 6 of 7 patients treated with open reduction and internal fixation, with maintenance of reduction at 26-month follow-up. 11 Several other studies have reported chronic pain in surgically treated pediatric patients as well, some with evidence of degenerative changes. 7 , 8 , 12 The full extent of radiographic and bony changes in the pediatric population, however, has not been adequately described, and long-term outcomes into adulthood are unknown.…”
Section: Discussionmentioning
confidence: 98%
“…There are few studies of Lisfranc injuries in children and thus the treatment strategies are based on the reported results applying to adults. Depending on the mechanism of injury and its result (ligamentous and/or osseous injury), different treatment options have been described including conservative treatment, use of k-wires and/or screws and/or plates[11,14,15]. These methods seem to offer really stable fixation but disadvantages and complications have been reported including screw breakage, reduced range of motion and pain of the affected area, extensive cartilage damage, prolonged immobilization period and need for additional procedures to remove the screws[16-19].…”
Section: Discussionmentioning
confidence: 99%
“…Literature dealing with Lisfranc injuries in adolescents/children are extremely limited (Table 2). Veijola et al[14] in their retrospective study included six patients (range 13 to 16 years) treated with ORIF. In all but one case, they achieved anatomical reduction, but most patients claimed discomfort in the injured foot.…”
Section: Discussionmentioning
confidence: 99%